Annotated record of the detailed examination of Mn deposits from DSDP Leg 25 (Sites 239, 242, 245, 245A, 248) - Leclaire, Lucien (Supplement to: Leclaire, L (1974): Late Cretaceous and Cenozoic Pelagic DepositsPaleoenvironment and Paleooceanography of the Central Western Indian Ocean. In: Simpson, E.S.W.; Schlich, R.; et al., Initial Reports of the Deep Sea Drilling Project, Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, XXV, 481-513, https://doi.org/10.2973/dsdp.proc.25.120.1974, 1974)
Pelagic deposits are the dominant contributors to the sediment layers that blanket ridges and basaltic sea floor in deep basins. Among pelagic constituents, nannofossils undoubtedly are the predominant contributor, especially to Cenozoic chalk and ooze. Among Leg 25 sites, the most typical pelagic deposits are found in the Madagascar Basin (Site 245) including a clayey nanno chalk, bearing Fe-Mn oxides, resting directly on the basalt and overlain successively by a nanno chalk which is interlayered with chert and devitrified volcanic ash and a nearly pure nanno ooze. The lithologic sequence is capped by brown clay. Upper Cenozoic foram sand and foram nanno ooze were found on the Mozambique Ridge (Site 249) and particularly on the Madagascar Ridge (Site 246). Biogenic silica-rich facies are rare and mainly located near the top of the lowest latitude sites.